Forty years later: Laurie Strode and the survival of the Final Girl. Issue 1 (1st March 2021) - Podraza, Morgan
The Final Girl trope is well established in horror, and the Final Girl's actions leading up to and including the moment of her 'triumph' over the monstrous threat have generated a rich vein of scholarly and popular discourse. However, the life and experiences of the Final Girl beyond the violent events that initially defined her have largely remained unexplored despite the repetitive appearance of characters like Laurie Strode across horror franchises. By pairing John Carpenter's 1978 Halloween and David Gordon Green's 2018 Halloween ‐ positioned as a direct sequel to the original film ‐ the life of the Final Girl beyond her confrontation with the monstrous threat is made visible, and the experiences and effects of trauma are centred. An analysis of the visual and narrative manifestations of Laurie Strode's experience of trauma makes clear the limits of the traditionally constructed trope by asking what it means to survive within horror franchises. Acknowledging the Final Girl as a survivor of trauma fosters new possibilities for how the Final Girl trope is discussed and calls attention to the ways that representations of trauma within the horror genre can reflect and reify the experiences of survivors in positive and productive ways.